A Critique On The Concept Of Sustainable Development - Ng, Amy Sing Fuay (Journal of Malaysian and Comparative Law, 2001)
As we look to the world today, one factor stands out glaringly, be it in the developed country or in a developing country, it is that, most of the current economic activities are not sustainable. Demands of a growing human population and an expanding global economy are placing increasing stresses on natural systems such as the forests, grasslands, wetlands and river systems which in turn threaten the very existence of diversity fo species.